In the Hot Seat: Behavioral Change and Old-Growth Trees Underpin an Australian Songbird’s Response to Extreme Heat - Sharpe, Lynda L.; Prober, Suzanne M.; Gardner, Janet L. (Frontiers in Ecology and Evolution, 2022)
Anthropogenic climate change is increasing the frequency and intensity of heat waves, thereby threatening biodiversity, particularly in hot, arid regions. Although free-ranging endotherms can use behavioral thermoregulation to contend with heat, it remains unclear to what degree behavior can buffer organisms from unprecedented temperatures. Thermoregulatory behaviors that facilitate dry heat loss during moderate heat become maladaptive once environmental temperatures exceed body temperature. Additionally, the costs associated with behavioral thermoregulation may become untenable with greater heat exposure, and effective cooling may be dependent upon the availability of specific microhabitats. Only by understanding the interplay of these three elements (responses, costs and habitat) can we hope to accurately predict how heat waves will impact wild endotherms. We quantified the thermoregulatory behaviors and microhabitat use of a small passerine, the Jacky Winter (Microeca fascinans), in the mallee woodland of SE Australia. At this location, the annual number of days ≥ 42°C has doubled over the last 25 years. The birds’ broad repertoire of behavioral responses to heat was nuanced and responsive to environmental conditions, but was associated with reduced foraging effort and increased foraging costs, accounting for the loss of body condition that occurs at high temperatures. By measuring microsite surface temperatures, which varied by up to 35°C at air temperatures > 44°C, we found that leaf-litter coverage and tree size were positively correlated with thermal buffering. Large mallee eucalypts were critical to the birds’ response to very high temperatures, providing high perches that facilitated convective cooling, the coolest tree-base temperatures and the greatest prevalence of tree-base crevices or hollows that were used as refuges at air temperatures > 38°C. Tree-base hollows, found only in large mallees, were cooler than all other microsites, averaging 2°C cooler than air temperature. Despite the plasticity of the birds’ response to heat, 29% of our habituated study population died when air temperatures reached a record-breaking 49°C, demonstrating the limits of behavioral thermoregulation and the potential vulnerability of organisms to climate change.